ANALISA PENGARUH ETOS KERJA, KONFLIK KERJA DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA PADA PT. MBI - Diovany Tirtana; Anggun Wijayanti (Universitas Ratu Samban, 2023)
This study aims to determine the influence of work ethic, work conflict and compensation on employee work productivity of distribution employees. The independent variables in this study are work ethic (X1), work conflict (X2), compensation (X3) and the dependent variable in this study is work productivity (Y). The population in this study were employees at the PT. Mega Bahtera Indonesia with a sample size of 31 people. This research uses quantitative research methods. The data analysis using SPSS vers 22 software and methods used is a data quality test consisting of a validity test and a realibility test, the classical assumption test consisting of a normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, multiple liniear regression analysis, T test and F test and un coefficient of determination.The result show that work ethic has a significant positive effect, work conflict has a significant negative effect and conpensation has a significant positive effect.